Falls and Fractures in the Elderly with Sinus Node Disease: The Impact of Pacemaker Implantation - Nazmi Krasniqi; Diana Segalada; Thomas F. Lüscher; Kurt Lippuner; Laurent Haegeli; Jan Steffel; Thomas Wolber; Corinna Brunckhorst; Johannes Holzmeister; David Hürlimann; Firat Duru (Cardiology Research and Practice)
Background. Falls and fractures in the elderly are among the leading causes of disability. We investigated whether pacemaker implantation prevents falls in patients with SND in a large cohort of patients. Methods. Patient demographics and medical history were collected prospectively. Fall history was retrospectively reconstituted from available medical records. The 10-year probability for major osteoporotic fractures was calculated retrospectively from available medical records using the Swiss fracture risk assessment tool FRAX-Switzerland. Results. During a mean observation period of 2.3 years after implantation, the rates of fallers and injured fallers with fracture were reduced to 15% and 6%, respectively. This corresponds to a relative reduction in the number of fallers of 75% (P<0.001) and of injured fallers of 63% (P=0.014) after pacemaker implantation. Similarly, the number of falls was reduced from 60 (48%) before pacemaker implantation to 22 (18%) thereafter (relative reduction 63%, P=0.035) and the number of falls with injury from 22 (18%) to 7 (6%), which corresponds to a relative reduction of 67%, P=0.013. Conclusion. In patients with SND, pacemaker implantation significantly reduces the number of patients experiencing falls, the total number of falls, and the risk for osteoporotic fractures.